Assessing The Impact of Water Quality on Freshwater Aquaculture: A Systematic Literature Review - Bastian, Ade; Mardiana, Ardi; Koswara, Engkos; Rifki, Muhammad (Journal of Applied Information System and Informatic (JAISI), 2025)
Water quality is a critical determinant of ecosystem sustainability and the productivity of freshwater aquaculture. This study performed a systematic literature review (SLR) to assess the impact of water quality on the growth, health, and yield of freshwater fish. The research examines contemporary technical advancements, such as Internet of Things (IoT) systems, unmanned aerial vehicles (UAVs), machine learning prediction models, and biotechnological methods for monitoring and managing water quality. The literature selection procedure employed the PRISMA framework and encompassed 136 articles sourced from the SCOPUS database. Following rigorous screening processes, three primary publications were chosen for additional examination. The review findings indicate that parameters like dissolved oxygen (DO), pH, ammonia, and temperature significantly influence fish health and production. Contemporary technologies, such IoT and UAVs, have demonstrated their capacity to enhance the effectiveness of water quality monitoring, whilst biotechnology provides novel options for the sustainable treatment of aquaculture waste. This research offers significant insights for scholars, policymakers, and practitioners in the advancement of more efficient and sustainable aquaculture methodologies.